Brand Product as a Competitive Advantage (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
The paper seeks to show the importance of building a brand of fruit and vegetable vendors in the market. The aim is to prove that good and quality low-priced products can generate more sales, win new customers and retain existing consumers. Methods of marketing research through the survey questionnaire brought to the knowledge and attitudes of marketers and consumers at the market. The results of the research provided a reliable basis for concluding that, based on marketing mix instruments and certain psychological and sociological attitudes and consumer thinking, higher sales of products on the market could be achieved. The conclusion is that products should be presented in an interesting and effective way to consumers, which will enable them to create their own brand in order to achieve economic effects.